2010
DOI: 10.1186/1476-7120-8-6
|View full text |Cite
|
Sign up to set email alerts
|

Playing games with a thrombus: a dangerous match. Paradoxical embolism from a huge central venous cathether thrombus: a case report

Abstract: Thromboembolism is a major cause of death in cancer patients. The association between paraneoplastic hypercoagulability of oncological patients and long-term central venous catheters (CVC) may result in CVC associated thrombosis. Patent Foramen Ovale (PFO), especially when associated with atrial septal aneurysm (ASA) is a risk factor for paradoxical embolism. We report a case of paradoxical embolism with stroke in an oncological patient with a huge CVC thrombus playing "ping-pong" with an hypermobile ASA with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…[26] Moreover, paraneoplastic hypercoagulability, chemotherapy and prolonged use of central venous catheters imply an increased risk of thromboembolism and consequently death. [27] The observation of a high mortality for non-neurological causes, also in our series, confirms that the modern treatments allow a significant control of the disease within the nervous system. Surgery entails the additional advantage of large tissue-samples availability for a detailed histological analysis that may influence targeted adjuvant therapies.…”
Section: Discussionsupporting
confidence: 85%
“…[26] Moreover, paraneoplastic hypercoagulability, chemotherapy and prolonged use of central venous catheters imply an increased risk of thromboembolism and consequently death. [27] The observation of a high mortality for non-neurological causes, also in our series, confirms that the modern treatments allow a significant control of the disease within the nervous system. Surgery entails the additional advantage of large tissue-samples availability for a detailed histological analysis that may influence targeted adjuvant therapies.…”
Section: Discussionsupporting
confidence: 85%
“…Intracardiac right‐to‐left shunting was demonstrated in 6 patients, while a pulmonary shunt was assumed in 9 patients. It has been shown that previously asymptomatic individuals may also harbor subtle right‐to‐left shunts, most commonly a patent foramen ovale (11%–35% of the healthy population) 6 , 9 , 10 . Paradoxical thromboembolism can occur through these shunts during hypercoagulable states.…”
Section: Discussionmentioning
confidence: 99%
“…Although paradoxical embolism through a PFO is a common cause of ischemic stroke, paradoxical embolic stroke associated with a central venous dialysis catheter (CVDC) is relatively uncommon and only a few cases among adult patients have been reported in the literature [7][8][9][10][11]. To the best of our knowledge, this is the first case of paradoxical embolism associated with the use of a tissue plasminogen activator (tPA) for unclogging a hemodialysis (HD) catheter.…”
Section: Introductionmentioning
confidence: 99%